Nematicidal Activity of Native Bacillus subtilis Against Reniform Nematode, Rotylenchulus reniformis Infesting Castor (Indian Journal of Nematology, 2025)
Castor (Ricinus communis L.) is one of the important non-edible oilseed crops infected by Rotylenchulus reniformis all over the world. The control of this nematode primarily relies on the chemical nematicides. With the growing concern of environmental safety, bio-management of nematodes has been gaining importance in recent years. In the present study, the effect of five indigenous Bacillus isolates was evaluated for their ability to control reniform nematode, Rotylenchulus reniformis population, and to improve the growth of the castor. Among the different isolates tested (BG31, BG37, BG42, BG57 and BG66), B. subtilis BG42 effectively suppressed egg hatching (96.2%) and induced maximum mortality of R. reniformis (77.8%) at 30% concentration. In pot trials, all the Bacillus species significantly reduced the root and soil population of nematode over untreated control. A minimum nematode root population of 23.7 females + 21.7 egg masses/g root was observed in the B. subtilis BG42-treated roots, while in untreated control it was 86.7 females + 66 egg masses/g root; soil population was also least (45/200 cc) compared to 253/200 cc soil in the untreated control. B. subtilis BG42also significantly improved plant growth parameters over other isolates and untreated control. In field studies also carried out for two seasons, B. subtilis BG42 induced maximum plant growth characteristics and maximum reduction in nematode population. The highest yield of 912.3 kg/ha was recorded with the same isolate.